Regionální identita obyvatel a rekreantů v pohraničí; případová studie: Bor na Tachovsku. - Sladká, Jana (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2011)
The thesis "Regional Identity of the Residents and Holiday-makers in the Borderlands; Case Study: Bor in the Tachov Region" aims on the assessment of the regional identity of the residents and holiday-makers in the border area of the Czech Republic- Bor region, and then finding of the awareness of the solidarity of the users of the area in which they are living and which they are using for the purpose of recreation. Beside the assessment of the regional identity in the Bor region the thesis aims on comparison of the research outcomes of the chosen area with the overall outcomes of the grant project number 43/03/1491 and finding specifics through the questionnaire survey and guided dialogues, including tabular and graphical representation of the outcomes. Another aim is the assessment of the regional identity based on the promotional materials. The model area of Bor in the Tachov region is an example of the border periphery of the Czech Republic where the forming of regional identity was deeply affected by the World War II and successive settlement.
Keywords: Bor (in the Tachov region); periferie; regional identity; Identita; Bor (Tachovsko); identita regionů; příhraničí; border; Identity; periphery